Correlation between Processing, Morphology and Impact Resistance of PBT/ABS Blends - Prezenszky,André Cortegoso (2017)
To understand the processing influence in an intermeshing corotating twin-screw extrusion (ICTSE) on the morphology and impact properties of the uncompatibilized PBT/ABS (70/30) blend, it was submitted to different processing parameters. In this way both morphology and impact properties (resistance and ductile brittle transition temperature (DBTT) would be a function of processing only, because there would be no influence of a compatibilizer. The rotation speed of the screws influenced both impact resistance and Ductile Brittle Transition Temperature (DBTT) of the PBT/ABS blends. Blends prepared with higher rotation speed (240 rpm) did not present toughness at room temperature, whereas the blends prepared at lower speed showed high impact strength at room temperature and DBTT near to 5 °C. The angle between the kneading blocks discs also influenced the impact properties, because blends processed with screw with 90º angle between kneading block disks, for two different feed rates, showed lower DBTT than the blends processed with 45º angle. The morphological analysis by TEM showed that blends processed at low rotation speed of the screws presented a higher dispersion degree than those processed at high rotation speed. Blends processed in screws where the angle between the disks was 90º showed a higher dispersion degree than the blends processed in disks with a 45º angle. These results are in agreement with the impact properties, confirming that high dispersion of the ABS particles improves the impact properties of the blend.